Notoatherix antiqua gen. et sp. nov., first fossil water snipe fly from the Late Jurassic of Australia (Diptera: Athericidae) - Oberprieler, Stefanie K.; Yeates, David K. (Zootaxa, 2014)
The first water snipe fly (Diptera: Tabanomorpha) fossil discovered in the Late Jurassic Talbragar Fish Bed in Australia is described and illustrated. Notoatherix antiqua gen. et sp. nov., described from a single wing specimen, is assigned to the family Athericidae based on the diagnostic feature of this family: the vein R2+3 ending very near to R1 (marginal cell closed). It is the first record of Athericidae from Australia and the oldest adult record of this family worldwide.